Seroprevalence, Accuracy and Precision Value of Brucellosis Surveillence at The Region Area of Balai Karantina Pertanian Kelas I Balikpapan - Faizal Rafiq; Notodipuro, Khairil Anwar; Oktarina, Sachnaz Desta; Mualifah, Laily Nissa; Pandansari, Niken; Hapsari, Linda Dwi (Media Kedokteran Hewan, 2023)
The Technical Implementation Unit alai Karantina Pertanian Kelas I Balikpapan plays a role in efforts to prevent the entry, spread, and release of HPHK. Direct observation was performed by surveying the target brucellosis in the region of Balai Karantina Pertanian Kelas I Balikpapan. This surveillance aimed to determine the seroprevalence of brucellosis and to support the maintenance of brucellosis status in East Kalimantan. Sampling in areas with reported clinical symptoms and brucellosis reactors. The sampling areas were based on the region of Balai Karantina Pertanian Kelas I Balikpapan in Balikpapan City, North Penajam Paser Regency, Paser Regency, and Kutai Kartanegara Regency. The method for calculating the number of samples to detect the disease uses the Rose Bengal Test (RBT) and Complement Fixation Test (CFT). The test results showed a seroprevalence of 0.29%, positive and negative predictive values of 50% and 99,7%, respectively, an accuracy value of 99.11%, and a precision of 50%. The test performance based on the accuracy value was excellent because it had a value of 99.11%, which means that the ability of the CFT to detect all samples tested correctly was 99.11%. The test carried out using the CFT test on this surveillance had a precision or test consistency of 50%, and the sensitivity and specificity were 50% and 99.7%, respectively.